A "Comma Sign"–Directed Subscapularis Repair in Anterosuperior Rotator Cuff Tears Yields Biomechanical Advantages in a Cadaveric Model. Issue 12 (October 2021) - Hackl, Michael; Buess, Eduard; Kammerlohr, Sandra; Nacov, Julia; Staat, Manfred; Leschinger, Tim; Müller, Lars P.; Wegmann, Kilian
Background: Additional stabilization of the "comma sign" in anterosuperior rotator cuff repair has been proposed to provide biomechanical benefits regarding stability of the repair. Purpose: This in vitro investigation aimed to investigate the influence of a comma sign–directed reconstruction technique for anterosuperior rotator cuff tears on the primary stability of the subscapularis tendon repair. Study Design: Controlled laboratory study. Methods: A total of 18 fresh-frozen cadaveric shoulders were used in this study. Anterosuperior rotator cuff tears (complete full-thickness tear of the supraspinatus and subscapularis tendons) were created, and supraspinatus repair was performed with a standard suture bridge technique. The subscapularis was repaired with either a (1) single-row or (2) comma sign technique. A high-resolution 3D camera system was used to analyze 3-mm and 5-mm gap formation at the subscapularis tendon-bone interface upon incremental cyclic loading. Moreover, the ultimate failure load of the repair was recorded. A Mann-Whitney test was used to assess significant differences between the 2 groups. Results: The comma sign repair withstood significantly more loading cycles than the single-row repair until 3-mm and 5-mm gap formation occurred ( P ≤ .047). The ultimate failure load did not reveal any significant differences when the 2 techniques were compared ( P = .596). Conclusion: The results of this study show that additional stabilization of the comma sign enhanced the primary stability of subscapularis tendon repair in anterosuperior rotator cuff tears. Although this stabilization did not seem to influence the ultimate failure load, it effectively decreased the micromotion at the tendon-bone interface during cyclic loading. Clinical Relevance: The proposed technique for stabilization of the comma sign has shown superior biomechanical properties in comparison with a single-row repair and might thus improve tendon healing. Further clinical research will be necessary to determine its influence on the functional outcome.